Síntese e caracterização do poli(ácido láctico) para potencial uso em sistemas de liberação controlada de fármacos - Carvalho, Ana Claúdia Medeiros de (2013)
With the advances in medicine, life expectancy of the world population has grown considerably in recent decades. Studies have been performed in order to maintain the quality of life through the development of new drugs and new surgical procedures. Biomaterials is an example of the researches to improve quality of life, and its use goes from the reconstruction of tissues and organs affected by diseases or other types of failure, to use in drug delivery system able to prolong the drug in the body and increase its bioavailability. Biopolymers are a class of biomaterials widely targeted by researchers since they have ideal properties for biomedical applications, such as high biocompatibility and biodegradability. Poly (lactic acid) (PLA) is a biopolymer used as a biomaterial and its monomer, lactic acid, is eliminated by the Krebs Cycle (citric acid cycle). It is possible to synthesize PLA through various synthesis routes, however, the direct polycondensation is cheaper due the use of few steps of polymerization. In this work we used experimental design (DOE) to produce PLAs with different molecular weight from the direct polycondensation of lactic acid, with characteristics suitable for use in drug delivery system (DDS). Through the experimental design it was noted that the time of esterification, in the direct polycondensation, is the most important stage to obtain a higher molecular weight. The Fourier Transform Infrared (FTIR) spectrograms obtained were equivalent to the PLAs available in the literature. Results of Differential Scanning Calorimetry (DSC) showed that all PLAs produced are semicrystalline with glass transition temperatures (Tgs) ranging between 36 - 48 °C, and melting temperatures (Tm) ranging from 117 to 130 °C. The PLAs molecular weight characterized from Size Exclusion Chromatography (SEC), varied from 1000 to 11,000 g/mol. PLAs obtained showed a fibrous morphology characterized by Scanning Electron Microscopy (SEM)